Comparation of combination between enamel matrix derivative (EMD) with synthetic bone graft and EMD with natural bone graft in intrabony defect treatment - Patimah; Arni Irawaty Djais; Mardiana Andi Adam (Makassar Dental Journal PDGI Makassar, 2020)
Objective: To compare the clinical outcome of combination between EMD with synthetic bone graft and EMD with natural bone graft in intrabony defect treatment. Methods: Online searches have been conducted on the PubMed and Wiley website January 2009-November 2018 using the keywords